2020
DOI: 10.1080/02678292.2020.1777474
|View full text |Cite
|
Sign up to set email alerts
|

Driving issues of large area liquid crystal devices

Abstract: The surface area of liquid crystal (LC) devices in different applications, such as displays, signage devices and smart windows is becoming larger and larger. The electrical driving of such devices does not pose many problems when working on centimetre sized devices. Different types of driving issues arise when up-scaling such devices to areas of several square meter, due to the fact that the thin-film transparent conductors used in these device exhibit a finite sheet conductivity. One of the resulting issues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…In our group Zhong et al [16] employed vinyl ether and thiol to fabricate PDLCs via the Markovnikov reaction and investigated the morphology and electro-optical properties of the films. Zhang et al [59] demonstrated that the thiol-acrylate systems could be used to produce PDLC films [51] 5…”
Section: Preparation Of Conventional Pdlc Composite Filmmentioning
confidence: 99%
“…In our group Zhong et al [16] employed vinyl ether and thiol to fabricate PDLCs via the Markovnikov reaction and investigated the morphology and electro-optical properties of the films. Zhang et al [59] demonstrated that the thiol-acrylate systems could be used to produce PDLC films [51] 5…”
Section: Preparation Of Conventional Pdlc Composite Filmmentioning
confidence: 99%